Australia's GAAR Turns 40: In its Prime or Mid-Life Crisis? - Stewart, Miranda (Victoria University of Wellington Law Review, 2022)
This article explores aspects of the legislative evolution of Australia's general anti-avoidance rule (GAAR) in pt IVA of the Income Tax Assessment Act 1936 (ITAA36) and considers how it shapes up after 40 years. It considers the legislative interaction of the GAAR with other parts of the income tax statute and explores the GAAR in an international context, including the Multinational Anti-Avoidance Law (MAAL) and Diverted Profits Tax (DPT) inserted into pt IVA. It concludes with consideration of the role and legitimacy of the GAAR in respect of both domestic and international economic and legal transactions.